2016
DOI: 10.1002/ajcp.12103
|View full text |Cite
|
Sign up to set email alerts
|

Action Civics for Promoting Civic Development: Main Effects of Program Participation and Differences by Project Characteristics

Abstract: Using both quantitative and qualitative data, this study examined the effect of participating in an action civics intervention, Generation Citizen (GC), on civic commitment, civic self-efficacy, and two forms of civic knowledge. The sample consisted of 617 middle and high schools students in 55 classrooms who participated, or were soon to participate, in Generation Citizen. Hierarchical linear models revealed that participating in Generation Citizen was associated with positive gains in action civics knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 54 publications
(59 reference statements)
3
30
0
Order By: Relevance
“…Approaches to more active civics education—also termed action civics —focus on engaging youth in meaningful political actions. The idea is that youth learn and practice commitments to political engagement by participating directly in political processes (Ballard, Cohen, & Littenberg‐Tobias, ). Action civics usually occurs in schools and involves young people identifying and researching a problem of interest and engaging in efforts to create change, a process similar to community‐based youth participatory action research (YPAR).…”
Section: Opportunities To Practice Being Politicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches to more active civics education—also termed action civics —focus on engaging youth in meaningful political actions. The idea is that youth learn and practice commitments to political engagement by participating directly in political processes (Ballard, Cohen, & Littenberg‐Tobias, ). Action civics usually occurs in schools and involves young people identifying and researching a problem of interest and engaging in efforts to create change, a process similar to community‐based youth participatory action research (YPAR).…”
Section: Opportunities To Practice Being Politicalmentioning
confidence: 99%
“…Action civics usually occurs in schools and involves young people identifying and researching a problem of interest and engaging in efforts to create change, a process similar to community‐based youth participatory action research (YPAR). Through action civics and YPAR, youth develop increased political efficacy, knowledge, critical reflection skills, and commitments to future political engagement (Ballard et al., ; Kirshner, ). Yet creating political change can be arduous and does not always succeed, so for some youth, action projects may lower political efficacy.…”
Section: Opportunities To Practice Being Politicalmentioning
confidence: 99%
“…Although YPAR has the potential to impact individuals, organizations, communities, practices, and policies, most of the empirical literature has focused on first-order change with respect to YPAR's effects on individual youth participants. This burgeoning literature has reported positive youth development outcomes in domains such as cognition, leadership, academics, social, and civic engagement (e.g., Anyon et al, 2018;Ballard, Cohen, & Littenberg-Tobias, 2016;Shamrova & Cummings, 2017;Voight & Velez, 2018). There is a smaller but growing literature that goes beyond first-order change: A recent systematic review identified 36 studies that reported effects of YPAR and related youth inquiry approaches on setting-level outcomes such as practitioner growth, programs, and policies (Kennedy, DeChants, Bender, & Anyon, 2019).…”
Section: Overview Of Literature and Key Implicationsmentioning
confidence: 99%
“…While community violence is inherently negative, civic engagement involves prosocial behaviors that enrich the broader community and address public issues (e.g., volunteering, voting, attending meetings) (Balsano, 2005;Chung & Probert, 2011;Cohen & Chaffee, 2013). Civic engagement can take many forms, such as joining community groups, working with bureaucrats, helping neighbors, or signing petitions (Fitzgerald, 2016); such activities can be grouped more broadly within grassroots activism, civic participation, dialogue across groups, and sociopolitical development (Checkoway & Aldana, 2013;Hope & Jagers, 2014). There are also diverse forms of civic activities more relevant today (Zaff, Boyd, Li, Lerner, & Lerner, 2010), given the changing social, political and technological contexts youth experience (Leventhal & Brooks-Gunn, 2003).…”
Section: Youth Civic Engagementmentioning
confidence: 99%